2020
DOI: 10.20858/sjsutst.2020.106.17
|View full text |Cite
|
Sign up to set email alerts
|

Canny Edge Detection Based Real-Time Intelligent Parking Management System

Abstract: Real-time traffic monitoring and parking are very important aspects for a better social and economic system. Python-based Intelligent Parking Management System (IPMS) module using a USB camera and a canny edge detection method was developed. The current situation of real-time parking slot was simultaneously checked, both online and via a mobile application, with a message of Parking "Available" or "Not available" for 10 parking slots. In addition, at the time entering in parking module, gate open and at the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…So, in a nutshell, camera-viewing angles, camera resolutions, and the heights at which cameras are situated are critical parameters for efficient real-time parking detection. The prototype model gives the best results in the articles by Trivedi et al (2017Trivedi et al ( , 2020aTrivedi et al ( , 2020b, when the camera is situated at 90 degree angles because it focuses only on specific parking locations with parked vehicles. Here, we assume the camera is situated at a height of 3 meters from the ground surface and at an angle of around 40 to 50 degrees.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…So, in a nutshell, camera-viewing angles, camera resolutions, and the heights at which cameras are situated are critical parameters for efficient real-time parking detection. The prototype model gives the best results in the articles by Trivedi et al (2017Trivedi et al ( , 2020aTrivedi et al ( , 2020b, when the camera is situated at 90 degree angles because it focuses only on specific parking locations with parked vehicles. Here, we assume the camera is situated at a height of 3 meters from the ground surface and at an angle of around 40 to 50 degrees.…”
Section: Discussionmentioning
confidence: 99%
“…A mono-camera-based parking module is explained by Davarci et al (2018) with the image-processing method, but a real-time parking demonstration is not presented in that study. A prototype model for a smart city parking system is established in Trivedi et al (2017Trivedi et al ( , 2020aTrivedi et al ( , 2020b; however, work for a real-time parking management system is not demonstrated there. A canny edge-detection-based real-time parking management system is explained in Trivedi et al (2020aTrivedi et al ( , 2020b with parking characteristics.…”
Section: Literature Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…The work presented in [ 17 ] have developed a simulation of the shared parking operation that considers the uncertainties with four parameters which are users, arrival, and departure time. The presented work in [ 18 ] involves the employment of a canny edge detection method and a USB camera to define the available parking slots. The work in [ 19 ] is used wireless vehicle detectors and magnetic sensors to define the availability of parking spaces.…”
Section: Related Workmentioning
confidence: 99%